Young Fu of the upper Yangtze - Lewis, Elizabeth Foreman 1892-1958 (Dell Publishing, 1973)
In the 1920's a Chinese youth from the country comes to Chungking with his mother where the bustling city offers adventure and his apprenticeship to a coppersmith brings good fortune.